National Strategic Project (Rempang EcoCity): Indigenous Peoples' Resistance in Responding to the Grabbing of Customary Land in Rempang Island - Aswad Asruddin, Fajar; Efendi , David (Dinasti Research, 2024)
The agrarian conflict in Rempang Island, Batam, centres on the construction of the Rempang Eco City National Strategic Project which requires the relocation of indigenous communities who have long lived there. This research aims to analyse indigenous peoples' resistance to the dispossession of customary land caused by the project, which threatens their existence. This research uses a qualitative approach with a literature study and secondary data analysis from online media coverage. Data was collected through NCapture with the keyword